A Formo in Contracts and Their Impact on Proving the Rights of the Contracting in Sharia and Law - Abdel Tawwab Moustafa Khaled Moawad (Fakultas Dakwah UIN KHAS Jember, 2025)
This study examines the concept of formality in contracts in a general manner by presenting the opinions of legal jurists, discussing them, and giving preference to the view the researcher considers most appropriate. It also clarifies the evidences for the legitimacy of formality in Islamic law, its significance, forms, means, and types, identifies the main contracts that fall within its scope, and explains the effects of non-compliance with formality in both Islamic law and positive law. The study concludes with several findings, the most important of which are that formality constituted the basis of contracting in Roman law, where emphasis was placed on the external form without regard to the concurrence of wills, and that it was also known among the Arabs through certain acts and gestures indicating the mutual consent of the parties. Positive law has tended to require adherence to formality alongside the realization of mutual consent, considering direct non-compliance with formality a cause for the nullity of the contract, while maintaining its validity in cases of indirect non-compliance. Islamic law, on the other hand, establishes mutual consent and the concurrence of wills as the foundation of a contract, subject to its conformity with the rules of Sharia, and does not impose specific formal requirements except when necessary or required to safeguard rights. In this way, Islamic law adopts a balanced position between the various theories, combining the validity of contract formation with the assurance of protecting rights.